(untitled) (Bangladesh Journal of Nuclear Agriculture, 2023)
Experiments were performed at farmers’ fields of five locations viz., Mymensingh, Sherpur, Jamalpur, Natore and Naogaon districts with two promising Boro rice mutants, RM-16(N)-8, RM-16(N)-10 and a check, BRRI dhan58 to evaluate some morpho-physiological features and its impact on grain yield. The experiment was setup in RCB design with three replications. Results revealed that high yielding genotypes, in general, showed superiority in morpho-physiological characters (leaf area, leaf area index, total dry mass production, absolute growth rate, relative growth rate, chlorophyll, total sugar and soluble protein content in leaves and harvest index) than the low yielding one. Results further indicated that genotype improvement efforts have achieved higher grain yield by higher growth rate at early growth stages and better assimilate partitioning to economic yield and short stature plants are unlikely to improve harvest index and resistant to lodging in rice. The mutant, RM-16(N)-10 had medium plant stature with greater biomass production capacity, superiority in growth and biochemical parameters and improve dry matter partitioning to economic yield which resulted higher number of grains panicle-1, thereby grain yield. In contrast, RM-16(N)-8 showed inferiority in morpho-physiological characters and performed the lowest yield attributes and grain yield. This information may be used in future plant breeding programme. Bangladesh J. Nuclear Agric, 37(2): 69-80, 2023